Genetic diversity and evolutionary history of the Schizothorax species complex in the Lancang River (upper Mekong) - Chen, Weitao (Ecol Evol, 2016)
The genus Schizothorax (Cyprinidae), one of the most diverse genera of ichthyofauna of the Qinghai‐Tibetan Plateau (QTP), is a good candidate for investigating patterns of genetic variation and evolutionary mechanisms. In this study, sequences from the mitochondrial control region, the cytochrome b gene, and two nuclear genes were used to re‐examine the genetic diversity and investigate the evolutionary history of the Schizothorax species complex inhabiting the Lancang River. Three maternal clades were detected in the Schizothorax species complex, but frequent nuclear allele sharing also occurred among the three maternal clades. A discrepancy between topologies of mitochondrial and nuclear loci might result from introgression or/and incomplete lineage sorting. The divergence of the clades of the Schizothorax species complex was closely related to the Late Pliocene and Early Pleistocene orogenesis of the QTP and Southwest Mountains of China. Demographic analyses indicated that the species complex subsequently persisted in situ with stable populations during Pleistocene glacial cycling, which suggested that Pleistocene climate changes did not exert a remarkable influence on the species complex. Our study provides a comprehensive analysis of the genetic diversity and evolutionary history of the Schizothorax species complex in the Lancang River.